2022
DOI: 10.1002/uog.23695
|View full text |Cite
|
Sign up to set email alerts
|

Decreased inferior vena cava diameter as an early marker in postpartum hemorrhage

Abstract: Objectives To examine the association between inferior vena cava (IVC) diameter and postpartum blood loss and assess whether IVC diameter is a useful marker in the evaluation of intravascular volume status in women with postpartum hemorrhage (PPH). Methods This was a prospective case–control study conducted in a university medical teaching center in Afula, Israel, between November 2018 and March 2020. The study cohort consisted of women with a singleton pregnancy who delivered vaginally at term. The PPH group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…The absence of methods that directly measure body volume status, with the paramount importance to accurately assess volume status in patients presenting to ED, necessitated the development of indirect measurement methods; such as the dilution techniques for the body fluids assessment, energy X‐ray absorptiometry, underwater weighing, air displacement plethysmography, bioelectrical impedance analysis, magnetic resonance, and computed tomography 19,20 . Although there is a growing need of a noninvasive tool to accomplish correct fluid management, the available methods are still nonoptimal, expensive and require long procedures and highly specialized personnel, so less invasive techniques such as respiratory CI of IVC with its' prompt identification of intravascular volume in critically ill patient especially in ED has been implemented in clinical use 10,21–26 …”
Section: Discussionmentioning
confidence: 99%
“…The absence of methods that directly measure body volume status, with the paramount importance to accurately assess volume status in patients presenting to ED, necessitated the development of indirect measurement methods; such as the dilution techniques for the body fluids assessment, energy X‐ray absorptiometry, underwater weighing, air displacement plethysmography, bioelectrical impedance analysis, magnetic resonance, and computed tomography 19,20 . Although there is a growing need of a noninvasive tool to accomplish correct fluid management, the available methods are still nonoptimal, expensive and require long procedures and highly specialized personnel, so less invasive techniques such as respiratory CI of IVC with its' prompt identification of intravascular volume in critically ill patient especially in ED has been implemented in clinical use 10,21–26 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the IVC collapse index decreases with increasing weeks of gestation [(40.8 ± 15.2)% at < 14 weeks of gestation, (32.6 ± 19.9)% at 20-28 weeks, and (26.5 ± 11.8%) at 28-34 weeks], with a rebound [(32.2 ± 19.9)%] by full term (> 27 weeks), with a significant difference (F = 3.557, P = 0.017), with < 14 weeks of gestation significantly higher than 28-34 weeks (P = 0.009) [11,12]. PVI is effective in determining changes in blood volume after general anesthesia combined with epidural block and has recently been used successfully in some studies to assess volume status in spontaneously breathing women [11,12]. The limitations of this study may lie in the fact that intraoperative PVI does not reflect maternal volume status because of the unstable tidal volume and surgical maneuvers during spontaneous breathing.…”
Section: Discussionmentioning
confidence: 99%
“…The Masimo ® Radical 7 (SET ® sensor) used in this study is more stable than the Masimo ® Radical 5 used in other studies, minimizing interference from autonomic respiratory variability. We believe that the combination of the PVI with the US measurement of the IVC-CI provides better sensitivity and enhanced specificity as a clinically valuable predictor of maternal volume in twin pregnancies [11,12]. Previous editions of the relevant guidelines recommended maternal measurement in the left lateral position and at end-expiration, with the latest version recommending the supine position, but due to the greater impact of the enlarged uterus on IVC reflux compression in the supine position in women with twin pregnancies, we have adopted a 15° left lateral position to reduce the impact on IVC [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hypovolemia is detected if the IVC IC is more than 50%. Traditionally, to visualize IVC, ultrasound probe is placed over the subxiphoid area (2)(3)(4)(5). Changes in the anterior-posterior IVC dimension is used to calculate the IC.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound assessment of inferior vena cava (IVC) collapsibility is performed to determine the volume status of spontaneously breathing and not mechanically ventilated critically ill patients. Conventional assessment is performed in patients in the supine position (1)(2)(3)(4)(5). In this case, a low-frequency ultrasound probe is placed over the subxiphoid area to visualize IVC where it enters the right atrium in a longitudinal section in B-mode.…”
Section: Introductionmentioning
confidence: 99%